2017
DOI: 10.1172/jci.insight.89169
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial microRNAs associated with reverse remodeling in human heart failure

Abstract: NIH 2R01 HL48013, 1R01 HL71118 (Bristow, PI); sponsored research agreements from Glaxo-SmithKline and AstraZeneca (Bristow, PI); NIH P20 HL101435 (Lowes, Port multi-PD/PI); sponsored research agreement from Miragen Therapeutics (Port, PI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…Recently, constituents from natural herbs have attracted attention with regard to pharmaceutical development. MicroRNA (miRNA), a small non‐coding RNA, is emerged as a critical node in post‐transcriptional regulation and a newly discovered class of gene regulatory factors at the core of human physiology and disease 3, 4. Increasing lines of evidence have been rapidly evolving for the crucial roles of miRNAs in regulating diverse aspects of cardiac function and progression of HF 4, 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, constituents from natural herbs have attracted attention with regard to pharmaceutical development. MicroRNA (miRNA), a small non‐coding RNA, is emerged as a critical node in post‐transcriptional regulation and a newly discovered class of gene regulatory factors at the core of human physiology and disease 3, 4. Increasing lines of evidence have been rapidly evolving for the crucial roles of miRNAs in regulating diverse aspects of cardiac function and progression of HF 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA), a small non‐coding RNA, is emerged as a critical node in post‐transcriptional regulation and a newly discovered class of gene regulatory factors at the core of human physiology and disease 3, 4. Increasing lines of evidence have been rapidly evolving for the crucial roles of miRNAs in regulating diverse aspects of cardiac function and progression of HF 4, 5. And notably microRNA‐1 (miR‐1), a cardiac‐enriched miRNA, is in most close relation to heart conditions, and the changes in its expression have been discovered in a variety of heart diseases 6, 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…DCM is described as dilation of the left ventricle as well as impaired systolic function with a reduced ejection fraction (2,11). As DCM progresses, the left ventricle wall starts to thin and becomes weak, causing the heart to be inefficient at pumping blood to the systemic circulation (2).…”
Section: Heart Disease Is a Major Public Health Problemmentioning
confidence: 99%
“…Studies have shown not only association of epigenetic changes with heart failure, but also epigenetic changes associated with reverse remodeling after treatment with a beta blocker or left ventricular assist device. 35,36 Miyamoto et al also showed that circulating miRs are differentially expressed between children with dilated cardiomyopathy who recover versus those requiring a transplant. 37 These differences may represent a valuable biomarker for risk stratification, as well as a potential molecular therapeutic target.…”
Section: Heart Failurementioning
confidence: 99%